LIZANKA’S WAYS TO COPE WITH THE IMPACTS OF HER PSYCHOLOGICAL PROBLEMS AS SEEN IN ANTON CHEKHOV’S A DOCTOR’S VISIT - ARIANTI, DEANE PUSPITA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Kata Kunci: Stress, Coping with the Stress, A Doctor’s Visit.Someone who faces the psychological problem in their life can keep it secretly. However, it has an impact for human’s life as stress causing psychological and physical disturbances. Thus, to overcome the impacts, person tries to find a way to cope with his psychological problem. It is reflected in A Doctor’s Visit by Anton Chekhov. The story tells about Lizanka who has psychological problems. Moreover, the psychological problems make her becomes stressful and bears it impacts, psychologically and physically. Thus, to cope with the impacts, she needs to solve her stress by finding solutions for her psychological problem.Therefore, this study uses stress and coping theory to analyze Lizanka’s ways in coping her psychological problems and its impacts. The result of this study shows that Lizanka can cope her psychological problem and its impacts that she bears by using several ways and by the attendancing and helping of Korolyov. The ways that she takes are seeking social support, and positive reappraisal. Thus, because of the presences and helps of Korolyov and also the coping ways that she takes, she seems relieved and sees her problem positively. As a result, it makes her not stressful anymore. For the next researchers, it is recommended to analyze A Doctor’s Visit from Freudian’s psychoanalysis point of view that is three systems of personality; id, ego and superego.